Institutionnalisation et usages d’un salariat libéral - Rémy Caveng (La Nouvelle Revue du Travail)
Polling companies enjoy a special legal status enabling them to employ workers under short-term independent contracts. Precariousness becomes a fact of life for people employed under such conditions. Having said that, the production constraints that companies face mean they also require a modicum stability in terms of workforce management. Hence the absence of any strict correlation between the instability characterising these workers’ employment status and their highly fragile employment relationships. Analysis of employee-manager transactions shows that this is a market based on asymmetrical relations akin to business relationships where employees are no longer treated as wage-earners but instead as self-employed individuals.